Unusual presentation of keratocystic odontogenic tumor: Two case reports - Sunitha Kesidi; Kotya Naik Maloth; Vinay Kumar Reddy Kundoor; Moni Thakur (Wolters Kluwer Medknow Publications, 2016)
Keratocystic odontogenic tumor (KOT) is a common odontogenic cyst with aggressive behavior with a high recurrence rate. Features that predict recurrence of KOT are thin friable epithelium which is difficult to enucleate and presence of satellite cysts in the fibrous wall. Most of the lesions grow in an anteroposterior direction without causing any bony expansion. Here, we report two cases of KOT with different clinical presentation.